PRESIDENTIAL POWER AND EXECUTIVE AGGRANDIZEMENT IN SHAPING THE CABINET - Febriansyah Ramadhan; Saiful Risky (Veritas et Justitia, 2025)
This article examines the President’s authority to determine the number of ministers and deputy ministers, which has the potential to result in an oversized cabinet that hinders oversight of the executive branch. Adopting a socio-legal approach that combines doctrinal analysis with the study of executive aggrandizement, this research maps the mechanisms through which normative flexibility enables the expansion of the cabinet. The main findings demonstrate that cabinet expansion through changes in the Law on State Ministries has operated at several levels as a means of consolidating executive power through political patronage, the politicization of the bureaucracy, and legal engineering. Cabinet expansion is not a new phenomenon in Indonesian political history; this pattern has recurred from the Old Order to the New Order era. Constitutional Court Decision No. 128/PUU-XXIII/2025 confirms that excessive Presidential power can hinder bureaucratic effectiveness and efficiency. The decision also strengthens claims of executive aggrandizement not only in the ministerial sector but also among deputy ministers. This article proposes restricting Presidential power, particularly in determining cabinet size, through constitutional regulation with clear quantitative limits. Clearly defined boundaries that are difficult to modify politically would provide an effective mechanism to restrain the President’s authority to expand the cabinet.